IBEM Simulation of Seismic Wave Scattering by a 3D Tunnel Mountain - Ping-Lin Jiang; Hua Jiang; Yu-Sheng Jiang; Dai Wang; Nan Li; Zhong-He Shi (Shock and Vibration)
The seismic wave scattering by a 3D tunnel mountain is investigated by the indirect boundary element method (IBEM). Without loss of generality, the 3D physical model of hemispherical tunnel mountain in an elastic half-space is established, and the influence of the incidence frequency and angle of P or SV wave on the mountain surface displacements is mainly examined. It is shown that there exists quite a difference between the spatial distribution of displacement amplitude under the incident P wave and the one under SV wave and that the incidence frequency and angle of wave, especially the existence of tunnel excavated in the mountain, have a great effect on the surface displacements of mountain; the presence of the tunnel in the mountain may cause the greater amplification of surface displacement, which is unfavorable to the mountain projects. In addition, it should be noted that the tunnel may suffer the more severe damage under the incident SV wave.